THE IMPACT OF UNREGULATED FACTOR INFLUENCE ON WINTER WHEAT GROWTH AND DEVELOPMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The modern meaning of accurate crop cultivation is closely associated with the new information technologies - geographic information and global positioning systems. Latvia has not published the results of research on soil conditions and the impact of unregulated factors of production conditions on winter wheat growth and yield. Analysis of results of studies aimed to clarify the difference of soil treatment facilities, as the criteria for the treatment of soil using soil characterizing Non-plant growth and development factors. Investigations were carried out in 2005 – 2007 on the production plantations of the Kurpnieki field, the Vecauce Study and Research Farm of the Latvia University of Agriculture. The results, while on a previous year, research on soil management measures to optimize the opportunities associated with global positioning systems, precision field management implementation practice shows that in order to obtain objective indicators and to gain the desired results, it was not enough for one season observation, since a large role in shaping the harvest is the meteorological conditions during the growing period. Unregulated factors: organic matter content, Ap horizon thickness, as well as the relative height above sea-level properties of materials research is the prerequisite for geographic information system-based resource-saving cultivation technology field-crop cultivation.